Intimate Partner Aggression and Marital Satisfaction: A Cross-Lagged Panel Analysis - Hammett, Julia F. (Journal of interpersonal violence, 2021)
Intimate partner aggression is common in dissatisfied relationships, yet it remains unclear whether intimate partner aggression is a correlate of relationship satisfaction, whether it predicts or follows from relationship satisfaction over time, or whether longitudinal associations are in fact bidirectional in nature. The present study evaluates these perspectives by examining self-reports of aggressive behaviors in relation to corresponding self-reports of relationship satisfaction among a sample of 431 low-income, ethnically diverse (76% Hispanic, 12% African American, 12% Caucasian) newlywed couples. Using a cross-lagged panel analysis, we examined associations between aggression and satisfaction across four time points, spaced by 9-month intervals, during the first 2.5 years of marriage. Cross-sectionally, less satisfied couples reported higher levels of intimate partner aggression. Longitudinally, aggression was a more consistent predictor of satisfaction than vice versa, though neither pathway was particularly robust: Intimate partner aggression was a significant predictor of relationship satisfaction at 4 of the 12 tested lags, whereas relationship satisfaction was a significant predictor of intimate partner aggression at only one of 12 lags. Because all effects were relatively weak and inconsistent, more specificity is needed to clarify circumstances under which aggression does and does not predict satisfaction, including whether the predictive power of the aggression-to-satisfaction association varies based on the severity of aggression or other individual (e.g., personality) or external (e.g., stress and environmental context) factors. Together, results indicate that dissatisfied couples are more likely to engage in intimate partner aggression, but being dissatisfied is unlikely to increase the level of aggression a couple engages in over time.